Information environment and participation of foreign banks in U.S. syndicated loan market - Chan, Ann Ling-Ching; Hsieh, Yi-Ting; Lee, Edward; Yueh, Meng-Lan (Journal of Banking & Finance, 2024)
This study examines how financial information quality affects the participation and lending behavior of foreign banks in the loan syndicate of U.S borrowers. We utilize the implementation of the Sarbanes-Oxley Act (SOX) in the U.S. as our research setting. We demonstrate a significant increase in foreign banks loan shares to public firms in the post-SOX period. In parallel, we find that this increase in lending by foreign banks is accompanied by more favorable price and non-price contract terms. By contrast, we find no evidence of either more loans or more favorable loan contract terms offered to U.S. privately held borrowers by foreign banks. Further analysis shows that the impact of such an exogenous change on loan contract terms are more pronounced among public listed borrowers with higher ex ante information asymmetry. Overall, our findings imply that the increase in quality and reliability of corporate financial information brought about by SOX reduces the information disadvantage of foreign lenders.